A Multi-Approach Investigation of Late Quaternary Lacustrine Sediments in Southern Jordan - AlShdaifat, Ahmad (2022)
Past lacustrine and wetland sediments from arid regions, sensitive to changes in precipitation and evaporation, are important archives of past environmental variability. This thesis presents new data that contribute to the Quaternary records of Jordan through multi-proxy analyses of sediment archives from two study sites in southern Jordan; the Gharandal Valley and the Dead Sea Basin. Through detailed analyses of the sediments from the two study sites, the depositional environments, environmental conditions, and how these changed, and to some extent their timing were reconstructed. Sediments from the Gharandal Valley were investigated and collected from five different sedimentary sections (> 30 m sediments) and analyzed for particle size distribution, organic and carbonate content (through LOI), and elemental (through XRF) and minerogenic (through magnetic susceptibility) composition. The results indicated complex tectonic/climate-driven depositional environments prevailed in the valley, during Marine Isotope Stage (MIS) 6, alternating from fluvial in-wash to fluvio-aeolian and wetland deposition following the proposed valley outlet damming. The GH1 and GH2, the main sections in the valley, record the environmental aggradation from stream-fed wetland depositional conditions where thin wetland beds developed following in-wash events, in the lower parts, into more consistent wetland (wetter) conditions towards the top of the sections. These cycles were identified in 16 fining upward primary associations in the GH1 section and 8 fining upward primary associations in the GH2 section. The age estimate (MIS6) is consistent with wet phases recorded elsewhere in the Levant and increased monsoon precipitation recorded in southern Arabia suggesting that an influence of the two systems (the northeastern Mediterranean Cyclones and the southern tropical monsoon), which do not reach the valley site today, may have contributed to maintaining the wetland conditions in the valley during glacial stadials and interstadials. From the eastern side of the Dead Sea Basin (DSB), the lacustrine section DS1 was investigated. The section is primarily comprised of laminated pale and dark laminae and laminated detrital laminae with a thick gypsum-dominated bed. Considering the different nature of the sediments, the DS1 bulk sediments were first analysed using proxies mentioned earlier for the Gharandal Valley. In addition, the pale laminae were analysed for the carbonate isotope composition (δ13C and δ18O), mineralogy (through XRD) and carbonate crystal habit (through SEM EDS) analysis. Through preliminary U/Th dating of aragonite laminae, the DS1 section age was estimated at ca. 40 ka to 37 ka (MIS3). This places the section as part of the Lake Lisan Middle Member (ca. 58 ka to 31ka). Based on the sediment’s lithology and the multi-proxy records, the environmental history of the DS1 section, of enhanced/reduced freshwater input into the lake (P/E ratio) at millennial, centennial and close to annual scales, is recorded in four distinct lithostratigraphic units. The units record relatively high lake levels, then lake level lowering and the deposition of the gypsum bed, a lake re-filling stage and return to stable relatively high lake levels. The environmental proxies suggest that during Greenland Interstadials (GIs), the lake level was relatively higher than during Stadials (GSs). The gypsum bed, the lowest relative lake level in the record, probably coincides with Heinrich Event 4. At centennial scales, the environmental proxies apparently record lake level changes corresponding to the GIs indicating variable amounts of freshwater reaching the DSB. An initial assessment of the moisture source was done based on the aragonite initial 234U/238U ratios variability and indicated the dominance of the Eastern Mediterranean cyclones in driving the deposition of the DS1 section. The results of this thesis emphasize southern Jordan’s sedimentological and palaeoclimatic heterogeneity and the complexity of the past environmental records that can be recovered. This indicates the need for continued investigations and particularly more dating control, based on more comprehensive and detailed approaches in order to achieve a better assessment of the Quaternary sedimentological and environmental variability in the region.